Family Socialization, Teacher Example, and Social Heterogeneity on the Diversity of Characters in the Global Profile of Pancasila Students - Yeni Susanti; Ravik Karsidi; Ahmad Zuber (Jurnal Pendidikan Indonesia, 2024)
This research was motivated by the development of the Merdeka Curriculum, whose implementation also focused on developing the character of the Pancasila Student Profile. One of the dimensions is the development of the character of Global Diversity, namely the habit of preserving noble culture, identity, locality and developing an open attitude in interactions with other cultures both on a national and global scale. The character of global diversity is a habit that is instilled from the family environment, school to society. In fact, there are still many conflicts caused by feelings of intolerance and discrimination, parents who only focus on their children's external needs and teachers who are unable to be role models. This research examines the influence between the intensity of family socialization, the level of teacher example and social heterogeneity on the level of global diversity character of Pancasila student profiles using a quantitative approach. This research is research with a quantitative approach, using a survey method with an explanatory research type. The results of this research show that the variables tested show a high category. Based on the results of the t test, it shows that there is a significant influence between the three dependent variables on the independent variables. The implication of this research is that teachers not only teach academic material, but also provide real examples of Pancasila values, such as integrity, cooperation and respect for differences.